2006
DOI: 10.4315/0362-028x-69.7.1552
|View full text |Cite
|
Sign up to set email alerts
|

A Predictive Model To Describe the Effects of Temperature, Sodium Lactate, and Sodium Diacetate on the Inactivation of a Serotype 4b Strain of Listeria monocytogenes in a Frankfurter Slurry

Abstract: A modified Gompertz equation was used to model the effects of temperature (55, 60, and 65ЊC), sodium lactate (0, 2.4, and 4.8%), and sodium diacetate (0, 0.125, and 0.25%) on inactivation of Listeria monocytogenes strain MFS 102 (serotype 4b) in frankfurter slurry. The effects of these factors were determined on the shouldering region (parameter A), maximum death rate (parameter B), and tailing region (parameter C) of microbial inactivation curves. Increased temperature or sodium diacetate concentrations incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Blom et al (3) already showed the advantage of using a combination of lactate and diacetate in sausage and cooked ham to inhibit the growth of L. monocytogenes. Recently, a predictive model to describe the effect of temperature, sodium lactate, and sodium diacetate on the inactivation of L. monocytogenes in frankfurter slurry has been introduced (22). Legan et al (10) developed the model, which describes the growth boundary of L. monocytogenes in ready-to-eat cooked meat products at 4ЊC as a function of the product salt, moisture, potassium lactate, and sodium diacetate concentration, and validated the conditions to prevent the growth of L. monocytogenes, using various cured and uncured products.…”
mentioning
confidence: 99%
“…Blom et al (3) already showed the advantage of using a combination of lactate and diacetate in sausage and cooked ham to inhibit the growth of L. monocytogenes. Recently, a predictive model to describe the effect of temperature, sodium lactate, and sodium diacetate on the inactivation of L. monocytogenes in frankfurter slurry has been introduced (22). Legan et al (10) developed the model, which describes the growth boundary of L. monocytogenes in ready-to-eat cooked meat products at 4ЊC as a function of the product salt, moisture, potassium lactate, and sodium diacetate concentration, and validated the conditions to prevent the growth of L. monocytogenes, using various cured and uncured products.…”
mentioning
confidence: 99%
“…Schultze et al . () reported that incorporating sodium lactate and SD in the frankfurter slurries had a significant ( P < 0.05) effect on increasing the heat tolerance. In this study, partial replacement of PL and SD with GTE and GSE increased heat sensitivity of L. monocytogenes in low‐ and high‐fat chicken hotdogs (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Another consideration in this study was that the frankfurter surface study did not include the acidulant salts that were used in the frankfurter slurries. From previous research in this laboratory (Schultze et al, 2006), it was determined that sodium lactate and sodium diacetate a Average values and standard deviations over three replicates for the negative inverse of the slope of the microbial survivor curve; different uppercase subscript letters represent significant differences (Po0.05) for each row.…”
Section: Heat Inactivation Studies On Frankfurter Surfacesmentioning
confidence: 99%